One-Sided Multiplier Approximation of Unbounded Functions - F. Hassan, Raad; K. Al-Saidy, Saheb; J. Al-Jawari, Naseif (Al-Nahrain Journal of Science, 2022)
The main objective of this article is to study the degree of best one-sided multiplier approximation of unbounded functions by means of the average modulus of smoothness by using sequences of algebraic polynomials Pn of degree less than n, n ³ r + 1, also in this search we shall prove a direct theorem by sequences Pn and some results.